Safety and efficacy of the therapeutic DNA-based vaccine VB10.16 in combination with atezolizumab in persistent, recurrent or metastatic HPV16-positive cervical cancer: a multicenter, single-arm phase 2a study - Hillemanns, Peter; Zikan, Michal; Forget, Frédéric; Denys, Hannelore G.; Baurain, Jean-Francois; Rob, Lukas; Woelber, Linn; Blecharz, Pawel; Bidzinski, Mariusz; Chovanec, Josef; Marmé, Frederik; Link, Theresa; et al. (Journal for ImmunoTherapy of Cancer, 2025)
Background Second-line treatment options for persistent, recurrent or metastatic (r/m) cervical cancer are limited. We investigated the safety, efficacy, and immunogenicity of the therapeutic DNA-based vaccine VB10.16 combined with the immune checkpoint inhibitor atezolizumab in patients with human papillomavirus (HPV)16-positive r/m cervical cancer.Patients and methods This multicenter, single-arm, phase 2a study ( NCT04405349, registered 26 May 2020) enrolled adult patients with persistent, r/m HPV16-positive cervical cancer. Patients received 3 mg VB10.16 (every 3 weeks (Q3W) for 12 weeks, hereafter every 6 weeks) combined with 1,200 mg atezolizumab (Q3W) for 48 weeks in total with a 12-month follow-up. The primary endpoints were incidence and severity of adverse events (AEs) and objective response rate (ORR; Response Evaluation Criteria in Solid Tumor V.1.1). ORR was assessed in the efficacy population, being all response-evaluable patients who received any administration of VB10.16 and atezolizumab and had at least one post-baseline imaging assessment.Results Between June 16, 2020, and January 25, 2022, 52 patients received at least one administration of study treatment. Of these, 47 patients had a minimum of one post-baseline tumor assessment. The median follow-up time for survival was 11.7 months. AEs related to VB10.16 were non-serious and mainly mild injection site reactions (9 of 52 patients). There were no signs of new toxicities other than what was already described with atezolizumab. ORR was 19.1% (95% CI 9.1% to 33.3%). Median duration of response was not reached (n.r.) (95% CI 2.2 to n.r.), median progression-free survival was 4.1 months (95% CI 2.1 to 6.2), and median overall survival was 21.3 months (95% CI 8.5 to n.r.). In programmed death-ligand 1 (PD-L1)-positive patients (n=24), ORR was 29.2% (95% CI 12.6 to 51.1). HPV16-specific T-cell responses were analyzed in 36 of 47 patients with an increase observed in 22/36 (61%).Conclusions The therapeutic DNA-based vaccine VB10.16 combined with atezolizumab was safe and well tolerated showing a promising clinically meaningful efficacy with durable responses in patients with persistent, r/m HPV16-positive cervical cancer, especially if PD-L1-positive.
Gesehen am 29.07.2025